(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2020)
Net energy metering (NEM) is a financial scheme that allows a consumer to generate, use and sell their excess energy to the grid. The main purpose of NEM is for self-consumption to reduce demand from the grid. It will allow customer to avoid being charged with expensive electricity tariff and hence reducing their monthly electricity bill. In other words, the annualized electricity cost could be reduced. NEM is commonly offered to residential solar photovoltaic (PV) system. Different PV size will determine the amount of energy that can be generated. This paper compares the annualized electricity cost of different residential customer types (large, medium and small) for different PV size under Malaysia’s net energy metering (NEM) scheme. This paper utilizes the load profile and solar irradiation data for Malaysia. The results show that high PV size does not guarantee reduction in annualized electricity cost especially for medium customers as the excess PV generation can only be accumulated for 24 months. Large customers may have benefited the most with lower annualized cost with larger PV system, while small customers may not have benefited at all.